Perinatal Mortality and Its Causes at Jinnah Postgraduate Medical Center, Karachi - Khan, Misbah; Naseeb, Shazia (Biological and Clinical Sciences Research Journal, 2025)
Perinatal mortality, according to the WHO, is the number of babies who die at or after 28 weeks of pregnancy or within seven days of birth. Perinatal mortality rate defines the health care status of a country. Pakistan specifically has a comparatively high perinatal mortality (PNMR), and it remains a challenge to improve maternal and neonatal health. Objective: To analyze perinatal mortality cases over a one-year period, from January 1st, 2023, to December 31st, 2023. Method: This study was conducted as a chart review of perinatal deaths that occurred in Ward 8 of Jinnah Postgraduate Medical Centre (JPMC) in Karachi in one year and determined major causes, including fetal asphyxia, congenital anomalies, placental complications, infection and low birth weight. Results: The PNMR was 60.5 per 1000 live births, and it revealed significant gaps needed for health improvement when compared with developed countries. Lack of antenatal care and ineffective antepartum and intrapartum care were major causes of high mortality levels. Conclusion: The study highlights the need for improving antenatal, intrapartum, and neonatal care, campaigns being run in the community and better ways of data management. These interventions can only prevent perinatal mortality and enhance maternal and newborn health in Pakistan.